Intertemporal effects of fiscal policy in an RBC model - Günter Coenen (Deutsche Bundesbank, 1998)
In the recent economic debate on the design of fiscal policy in Germany it is gene rally agreed that the total hurden of taxes and levies has to be reduced. In this paper, arguments that form the basis of this claim are evaluated within a calihrated Real Business Cycle model. The analysis shows that reducing taxes and levies induces an increase in economic activity as weB as positive welfare effects as long as government consumption has a low enough weight in the utility function of the households. Within the model the decrease in government receipts due to the reduction in taxes and levies is balanced by a redudion in government consumption according to a fiscal closure rule which guarantees a stable debt-to-output ratio.
Keywords: 330; Haushaltskonsolidierung; Steuerpolitik; Real Business Cycle; Intertemporales Gleichgewicht; Ökonometrisches Makromodell; Schätzung; Wohlfahrtsanalyse; Theorie; Deutschland